The role of infrastructure and government policies in determining the efficiency of Kenya's maize marketing system in the post-liberalization era - Karugia, Joseph T.; Wambugu, Stephen K.; Oluoch-Kosura, Willis (International Food Policy Research Institute, 2004)
This brief is based on the results of a research project funded under the competitive grants program of the 2020 Vision Network for East Africa. A research report with the same title is available on IFPRI’s website (www.ifpri.org) and also upon request. Background Liberalization of agricultural markets in Kenya in the 1990s was supposed to lead, among other things, to improved procurement and distribution of key agricultural commodities, especially foodstuffs.